2023
DOI: 10.3389/fcvm.2022.1035896
|View full text |Cite
|
Sign up to set email alerts
|

Bradycardia unresponded to atropin testing was successfully treated with therapeutic plasma exchange in a patient with severe COVID-19 complicated by Guillain-Barré syndrome: A case report

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has been an alarming situation worldwide for the past 2 years. The symptoms of coronavirus disease 2019 (COVID-19) are not only confined to the respiratory system but also affect a multitude of organ systems. Bradycardia associated with Guillain-Barré syndrome (GBS) is a rare autonomic and peripheral neurological complication of COVID-19. In this case report, we present the case of a 26-year-old man diagnosed with bradycardia associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…These authors also demonstrated the parameters that have been independently associated with ICU survival are SOFA (Sequential Organ Failure Assessment)–day 1, remdesivir use, AKI (acute kidney injury), sepsis, enteral insufficiency, duration of ICU stay and white blood cells. Our previous reports also revealed the severity of patients hospitalized in ICU who needed to have the optimal treatment with mechanical ventilation or therapeutic plasma exchange were related to AKI, pregnancy, and acute neurological complications [ 50 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…These authors also demonstrated the parameters that have been independently associated with ICU survival are SOFA (Sequential Organ Failure Assessment)–day 1, remdesivir use, AKI (acute kidney injury), sepsis, enteral insufficiency, duration of ICU stay and white blood cells. Our previous reports also revealed the severity of patients hospitalized in ICU who needed to have the optimal treatment with mechanical ventilation or therapeutic plasma exchange were related to AKI, pregnancy, and acute neurological complications [ 50 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent one of the first confirmed occurrence of GBS-associated SARS-CoV-2 infection reported in 2020, and numerous cases have been published during the COVID-19 pandemic. 34 Electroencephalographic (EEG) of patients with COVID-19 symptoms. revealed electroencephalographic abnormalities.…”
Section: Neurological Involvement In Novel Coronavirusmentioning
confidence: 99%
“…Subsequent one of the first confirmed occurrence of GBS-associated SARS-CoV-2 infection reported in 2020, and numerous cases have been published during the COVID-19 pandemic. 34 Electroencephalographic (EEG) of patients with COVID-19 symptoms. revealed electroencephalographic abnormalities.…”
Section: Neurological Involvement In Novel Coronavirusmentioning
confidence: 99%